IN VITRO PROPAGATION OF DROSERA INTERMEDIA AS INFLUENCED BY CYTOKININS, PH, SUCROSE, AND NUTRIENT CONCENTRATION - Rejthar, Jindrich; Viehmannova, Iva; Cepkova, Petra Hlasna; Fernández, Eloy; Milella, Luigi (Emirates Journal of Food and Agriculture, 2014)
This study was aimed to optimize in vitro propagation of Drosera intermedia for commercial and conservation purposes. The effect of concentration of MS nutrients (? MS, ¼ MS, ½ MS and, MS), various pH (3.7-7.7), sucrose concentration (10-40 g l-1) and cytokinins (0.1-3 mg l-1), namely BA (N6-benzyladenine), kinetin and zeatin were evaluated. After 60 days of shoot cultivation, growth and developmental characteristics (plant height, number of shoots per explant, diameter of rosette, number of roots per explant, length of roots) were recorded. No significant differences were found for various levels of pH and sucrose. On the contrary, plant height was negatively influenced by an increase of nutrients in the medium. The plants on 1/8 MS medium were significantly taller, and displayed higher proliferation capacity compared with those cultivated on full-strength MS medium. Shoot multiplication and growth was suppressed by supplementation of BA and kinetin, regardless of concentration used. Zeatin at the lowest concentration (0.1 mg l-1) provided the best results for shoot proliferation of all 26 treatments and can be recommended for micropropagation of D. intermedia.